Assessing feedback practices in classroom assessment at federal government educational institutions of Lahore, Pakistan - Syed Kamran Ali Shah; Zahida Habib (International Journal of Evaluation and Research in Education (IJERE), 2022)
This study aimed at investigating current feedback practices in classroom assessment. A sample of 300 participants including 150 teachers and 150 students each was selected using a stratified random sampling technique. Under the positivist paradigm, a survey method was deployed to conduct the research. In this study, a self-developed questionnaire comprising 20 items was used for data collection from the participants. The collected data was analyzed using SPSS (24.0). Frequencies and percentages were calculated in descriptive stats, whereas an independent sample t-test was used to verify research hypotheses. The study explored that class tests, class exercises, homework, and trial work during lessons were the most commonly used assessment tools whereas essay-type questions, and multiple-type questions were the most commonly used assessment formats. Moreover, it was found that delayed marking and returning of assessment tasks, less or no motivation for better performance, and lack of contact with parents were the major issues in feedback on classroom assessment at Federal Government Educational Institutions (FGEIs). The study recommended that the workload of teachers should be reduced so that they may have sufficient time to design and evaluate assessment tasks. Professional training on assessment on regular basis may be arranged for the faculty. A comprehensive plan of classroom assessment may be proposed by school principals along with a defined syllabus and be timely communicated the same to all stakeholders. An effective mechanism of monitoring to assess classroom assessment feedback practices may also be established.